O método das trajectórias clássicas: colisões coplanares do tipo A+BC - Marques, Jorge M. C. (2003)
The general methodology of classical trajectories as applied to elementary chemical reactions of the A+BC type is presented. The goal is to elucidate students about the main theoretical features and potentialities in applying this versatile method to calculate the dynamical properties of reactive systems. Only the methodology for two-dimensional (2D) case is described, from which the general theory for 3D follows straightforwardly. The adopted point of view is, as much as possible, that of allowing a direct translation of the concepts into a working program. An application to the reaction O(1D)+H2→O+OH with relevance in atmospheric chemistry is also presented. The FORTRAN codes used are available through the web page www.qqesc.qui.uc.pt.